Historia (hyper)textus, historia digitalis (Kirja-arvostelu) - Mikko Kainulainen (Suomen kasvatuksen ja koulutuksen historian seura., 2022)
Arvostelu teoksesta: Milligan, Ian 2019. History in the Age of Abundance? How the Web Is Transforming Historical Research. Montreal & Kingston: McGill-Queen’s University Press. 310.